STRATEGI IMPLEMENTASI DAN PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS TEACHING FACTORY DALAM MENINGKATKAN KUALITAS PENDIDIKAN KEJURUAN DI INDONESIA - Yogi Pradana (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
Vocational Education has a very important role in improving the quality of human resources in Indonesia. Referring to the function of education as stated in National Education, the function is to develop abilities and shape the character and civilization of the nation. The phenomenon shows that vocational school graduates do not have sufficient competence to possess them. The type of method used by the author in compiling this article is phenomenological research with a qualitative approach to literature study. Teaching factory can be defined as an industry-based learning model (products and services). In general, the aim of teaching factory learning is to increase work readiness, align competencies and build the work character of vocational school graduates according to the demands of the world of business and industry through a product/servicebased learning process (Learning Tools engineering). which is held in the environment, atmosphere, governance and rules or what is known as SOP in the actual workplace or industrial world. Through the teaching factory, students are taught to practice not only their cognitive abilities, students also learn to work in groups, train themselves students can communicate with other people and gain real experience and be trained to carry it out when entering the world of work. Students will also get more time to practice. Students are expected to be able to learn more optimally in developing their potential through learning from experiences they have had at school and during industrial work practice, compared to getting a lot of material in class but being less competent in your field. It is hoped that the corporate atmosphere created in teaching factory learning can further improve student competence. Implementation of Teaching Factory Determination of Goods and Services Teaching Factory Management Production Process Quality Control Evaluation Process Teaching Factory is an industry-based learning model where schools collaborate with the Business and Industrial World to produce competent graduates according to market needs. The aim of the Teaching Factory is to increase work readiness, align competencies, and build the work character of vocational school graduates in accordance with industry demands